2020
DOI: 10.1093/jee/toaa119
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects of Organic Products on Telenomus podisi (Hymenoptera: Platygastridae)

Abstract: Telenomus podisi Ashmead, 1893 is an important biocontrol agent, both in conventional and organic production systems. It can be used in association with other control strategies, such as natural botanical products and biological insecticides. Studies of selectivity and side effects are fundamental for proper management of insect control strategies because the interaction between different control strategies may negatively affect T. podisi. In this context, the present study evaluated the side effects of commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The longevity (L) and the egg-adult period (Po) were calculated using a weighted average as per Battisti et al (2020):…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The longevity (L) and the egg-adult period (Po) were calculated using a weighted average as per Battisti et al (2020):…”
Section: Resultsmentioning
confidence: 99%
“…According to Potrich et al, (2009) parasitism is considered the main factor for the efficiency of parasitoids in the field. Battisti et al (2020) also observed that when the parental females of T. podisi are exposed to Metarril® and Boveril® products, applied on the host eggs, the percentage of parasitism and the percentage of offspring emergence are not affected. It is important to point out that these extreme conditions of contact will hardly occur in the field, as the parasitoid can fly and seek other environments and/or its host's eggs.…”
Section: Conflict Of Interest Declarationmentioning
confidence: 87%
See 1 more Smart Citation